Illiteracy, dementia risk, and cognitive trajectories among older adults with low education - Arce Rentería, Miguel (Neurology, 2019)
OBJECTIVE: To investigate whether illiteracy was associated with greater risk of prevalent and incident dementia and more rapid cognitive decline among older adults with low education. METHODS: Analyses included 983 adults (≥65 years old, ≤4 years of schooling) who participated in a longitudinal community aging study. Literacy was self-reported (“Did you ever learn to read or write?”). Neuropsychological measures of memory, language, and visuospatial abilities were administered at baseline and at follow-ups (median [range] 3.49 years [0–23]). At each visit, functional, cognitive, and medical data were reviewed and a dementia diagnosis was made using standard criteria. Logistic regression and Cox proportional hazards models evaluated the association of literacy with prevalent and incident dementia, respectively, while latent growth curve models evaluated the effect of literacy on cognitive trajectories, adjusting for relevant demographic and medical covariates. RESULTS: Illiterate participants were almost 3 times as likely to have dementia at baseline compared to literate participants. Among those who did not have dementia at baseline, illiterate participants were twice as likely to develop dementia. While illiterate participants showed worse memory, language, and visuospatial functioning at baseline than literate participants, literacy was not associated with rate of cognitive decline. CONCLUSION: We found that illiteracy was independently associated with higher risk of prevalent and incident dementia, but not with a more rapid rate of cognitive decline. The independent effect of illiteracy on dementia risk may be through a lower range of cognitive function, which is closer to diagnostic thresholds for dementia than the range of literate participants.